2004
DOI: 10.1523/jneurosci.1323-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

GABAAReceptor Phospho-Dependent Modulation Is Regulated by Phospholipase C-Related Inactive Protein Type 1, a Novel Protein Phosphatase 1 Anchoring Protein

Abstract: GABAAreceptors are critical in controlling neuronal activity. Here, we examined the role for phospholipase C-related inactive protein type 1 (PRIP-1), which binds and inactivates protein phosphatase 1α (PP1α) in facilitating GABAAreceptor phospho-dependent regulation usingPRIP-1-/-mice. In wild-type animals, robust phosphorylation and functional modulation of GABAAreceptors containing β3 subunits by cAMP-dependent protein kinase was evident, which was diminished inPRIP-1-/-mice.PRIP-1-/-mice exhibited enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
129
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(137 citation statements)
references
References 47 publications
6
129
2
Order By: Relevance
“…Because PP1 and PP2A to a lesser extent appear to be responsible for dephosphorylation, PRIP could be a promising molecule because PRIP associates with both phosphatases, as described above. Furthermore, we have previously shown that PRIP plays an important role in controlling GABA A receptor activity via regulation of the phospho-states of the ␤ subunit of the receptor (53). In this case, PRIP was found to interact with GABA A receptor ␤ subunit, which was also a substrate of PP1.…”
Section: Discussionmentioning
confidence: 95%
“…Because PP1 and PP2A to a lesser extent appear to be responsible for dephosphorylation, PRIP could be a promising molecule because PRIP associates with both phosphatases, as described above. Furthermore, we have previously shown that PRIP plays an important role in controlling GABA A receptor activity via regulation of the phospho-states of the ␤ subunit of the receptor (53). In this case, PRIP was found to interact with GABA A receptor ␤ subunit, which was also a substrate of PP1.…”
Section: Discussionmentioning
confidence: 95%
“…Immunoprecipitation and GST Protein Pulldown AssayCo-immunoprecipitation assays and GST pulldown assays were performed as described previously (17,19). Briefly, the lysate obtained from COS7 cells transfected with the full-length rPRIP-1/pSG5 and PP2Ac/pRK5-Myc plasmid, cultured rat cortical neurons (21 DIV), or mouse brains was subjected to immunoprecipitation with rabbit control IgG, rabbit polyclonal anti-Myc antibody (c-Myc (A-14); Santa Cruz Biotechnology, Santa Cruz, CA), or rabbit polyclonal anti-PRIP-1 antibody, followed by the addition of 20 l of 50% slurry of protein G-Sepharose beads (Amersham Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that PRIP-1 plays an important role in the modulation of GABA A receptor function by regulating the receptor trafficking (19) and phosphorylation (17). To test whether PRIP proteins contribute to the observed BDNFdependent alterations of GABA A receptor activity (2-5), we have carried out experiments using PRIP-DKO mice, because PRIP-DKO mice became available recently as described above.…”
Section: Regulation Of Gaba a Receptor Currents By Bdnf In Hippocampamentioning
confidence: 99%
See 2 more Smart Citations